2005
DOI: 10.3201/eid1110.041276
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Cleaning Products and Drug Resistance

Abstract: Levels of antimicrobial drug resistance did not differ significantly between persons in households that used antibacterial cleaning and hygiene products and those that did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 18 publications
1
38
0
1
Order By: Relevance
“…Also, the study data showed a definitive lack of antibiotic/antibacterial cross-resistance when the most resistant staphylococci in each category were comparatively assessed across the three participant groups. These study results confirm similar findings from previous assessments of antibiotic and antibacterial resistance in home environments [2,3] and further discount claims that the use of antibacterial wash products have contributed to the selection and propagation of drug-resistant bacteria on human skin in the community to this time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, the study data showed a definitive lack of antibiotic/antibacterial cross-resistance when the most resistant staphylococci in each category were comparatively assessed across the three participant groups. These study results confirm similar findings from previous assessments of antibiotic and antibacterial resistance in home environments [2,3] and further discount claims that the use of antibacterial wash products have contributed to the selection and propagation of drug-resistant bacteria on human skin in the community to this time.…”
Section: Discussionsupporting
confidence: 91%
“…Published data have indicated that triclosan, one of the most widely used topical antibacterial agents, functions intracellularly as a site-directed enzyme inhibitor much like an antibiotic [1]. Although there are similarities in the mechanisms of antibacterial wash product actives and antibiotics, there has been very limited evidence that there is a correlation between antibiotic and antibacterial agent resistance in community bacteria associated with humans [2][3][4]. In this regard, there has been a call for more research [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, heavy metals and biocides such zinc (Peltier et al 2010) and triclosan (Ciusa et al 2012;Aiello et al 2005) can promote AR in bacteria in a process known as cross-selection (Martinez 2009a). In this context, WWTPs are a favorable environment for propagation of AR because they assemble high concentrations of bacteria (often in biofilms), nutrients, and antimicrobial agents (LaPara et al 2011;Novo and Manaia 2010;Xi et al 2009;DaCosta et al 2006).…”
Section: Release Of Arb and Args From Wwtpsmentioning
confidence: 99%
“…Concern has been raised about the potential evolution of bacteria resistant to triclosan. 40 In vitro experiments have suggested a link between exposure to biocides and resistance to antimicrobials; however, this remains a theoretical concern because there is little evidence showing that use of biocides in the community has led to the emergence and spread of antimicrobial-resistant pathogens. 41 There is evidence to support the use of alcohol-based hand rubs to break the chain of transmission of microorganisms.…”
Section: Prevention and Control Of Infectionsmentioning
confidence: 99%